Analyzing Internal and External Factors Contributing to Students' Learning Difficulties in Elementary Social Studies - Fitriyawati Karim (Journal of Education and Teaching Learning, 2025)
Social Studies (IPS) is fundamentally designed to develop elementary students' social competencies; however, it is frequently perceived as a difficult and uninteresting subject. This study aims to identify and analyze the specific internal and external factors causing students' learning difficulties in IPS at SDN 09 Duhiadaa. Employing a qualitative descriptive method, the research data were systematically collected through participatory observation, in-depth interviews with teachers and students, and documentation study. The data were analyzed using the Miles and Huberman interactive model. The findings revealed that learning difficulties stem from a complex interplay of internal and external factors. Internally, students exhibited a profound lack of interest, difficulty in grasping abstract social concepts, and poor memory retention. Externally, the difficulties were heavily exacerbated by the school environment—specifically the teacher's reliance on conventional lecturing methods and an extreme lack of instructional media. Furthermore, the un-fenced school environment bordered by rubber plantations served as a massive physical distraction. From the family environment, parents' low educational backgrounds and busy working schedules resulted in a total absence of academic guidance at home. In conclusion, overcoming IPS learning difficulties requires a synergistic approach involving pedagogical innovation by teachers and increased parental involvement to create a supportive learning ecosystem.